Synthesis, Isolation and Crystal Structures of the Metalated Ylides [Cy3P‐C‐SO2Tol]M (M = Li, Na, K). Issue 13 (22nd April 2020) - Darmandeh, Heidar; Scherpf, Thorsten; Feichtner, Kai‐Stephan; Schwarz, Christopher; Gessner, Viktoria H.
Abstract : The preparation and isolation of the metalated ylides [Cy3 PCSO2 Tol]M ( Cy 1‐M ) (with M = Li, Na, K) are reported. In contrast to its triphenylphosphonium analogue the synthesis of Cy 1‐M revealed to be less straight forward. Synthetic routes to the phosphonium salt precursor Cy 1 ‐H2 via different methods revealed to be unsuccessful or low‐yielding. However, nucleophilic attack of the ylide Cy3 P = CH2 at toluenesulfonyl fluoride under basic conditions proved to be a high‐yielding method directly leading to the ylide Cy 1‐H . Metalation to the yldiides was finally achieved with strong bases such as n BuLi, NaNH2, or BnK. In the solid state, the lithium compound forms a tetrameric structure consisting of a (C–S–O–Li)4 macrocycle, which incorporates an additional molecule of lithium iodide. The potassium compound forms a C 4 ‐symmetric structure with a (K4 O4 )2 octahedral prism as central structural motif. Upon deprotonation the P–C–S linkage undergoes a remarkable contraction typical for metalated ylides. Abstract :